Downregulation of the activating NKp30 ligand B7-H6 by HDAC inhibitors impairs tumor cell recognition by NK cells - Fiegler, Nathalie; Textor, Sonja; Arnold, Annette; Rölle, Alexander; Oehme, Ina; Breuhahn, Kai; Moldenhauer, Gerhard; Witzens-Harig, Mathias; Cerwenka, Adelheid (Blood, 2013)
Natural killer (NK) cells are central effector cells during innate immune responses against cancer. Natural cytotoxicity receptors expressed by NK cells such as NKp30 are involved in the recognition of transformed cells. Recently, the novel B7 family member B7-H6, which is expressed on the cell surface of various tumor cells including hematological malignancies, was identified as an activating ligand for NKp30. To investigate expression and regulation of B7-H6, we generated monoclonal antibodies. Our study reveals that B7-H6 surface protein and messenger RNA (mRNA) expression in various tumor cell lines was downregulated upon treatment with pan- or class I histone deacetylase inhibitors (HDACi) as well as after small interfering RNA-mediated knockdown of the class I histone deacetylases (HDAC) 2 or 3. B7-H6 downregulation was associated with decreased B7-H6 reporter activity and reduced histone acetylation at the B7-H6 promoter. In certain primary lymphoma and hepatocellular carcinoma samples, B7-H6 mRNA levels were elevated and correlated with HDAC3 expression. Finally, downregulation of B7-H6 on tumor cells by HDACi reduced NKp30-dependent effector functions of NK cells. Thus, we identified a novel mechanism that governs B7-H6 expression in tumor cells that has implications for potential cancer treatments combining immunotherapy with HDACi.
Gesehen am 15.03.2021